ADAP Promotes Degranulation and Migration of NK Cells Primed During in vivo Listeria monocytogenes Infection in Mice - Böning, Martha A. L.; Trittel, Stephanie; Riese, Peggy; van Ham, Marco; Heyner, Maxi; Voss, Martin; Parzmair, Gerald P.; Klawonn, Frank; Jeron, Andreas; Guzman, Carlos A.; Jänsch, Lothar; Schraven, Burkhart; et al. (Frontiers in Immunology, 2020)
The adhesion and degranulation-promoting protein (ADAP) serves as a multifunctional scaffold and is involved in the formation of immune signaling complexes. To date only limited and moreover conflicting data exist regarding the role of ADAP in NK cells. To extend existing knowledge we investigated ADAP-dependency of NK cells in the context of in vivo infection with the intracellular pathogen Listeria monocytogenes (Lm). Ex vivo analysis of infection-primed NK cells revealed impaired cytotoxic capacity in NK cells lacking ADAP as indicated by reduced CD107a surface expression and inefficient perforin production. However, ADAP-deficiency had no global effect on NK cell morphology or intracellular distribution of CD107a-containing vesicles. Proteomic definition of ADAPko and wild type NK cells did not uncover obvious differences in protein composition during the steady state and moreover, similar early response patterns were induced in NK cells upon infection independent of the genotype. In line with protein network analyses that suggested an altered migration phenotype in naïve ADAPko NK cells, in vitro migration assays uncovered significantly reduced migration of both naïve as well as infection-primed ADAPko NK cells compared to wild type NK cells. Notably, this migration defect was associated with a significantly reduced expression of the integrin CD11a on the surface of splenic ADAP-deficient NK cells one day post Lm infection. We propose that ADAP-dependent alterations in integrin expression might account at least in part for the fact that during in vivo infection significantly lower numbers of ADAPko NK cells accumulate in the spleen i.e. the site of infection. In conclusion, we show here that during systemic Lm infection in mice ADAP is essential for efficient cytotoxic capacity and migration of NK cells.